(untitled) (Veterinary Science, 2017)
Canine mammary tumors (CMT) represent nearly half of bitch’s neoplasias. The etiopathogeny of CMT is multifactorial. Both the protective effect of early ovarioectomy and steroid hormone receptors present in the tumor tissues show that the hormonal factor is involved in the development of mammary tumors. Clinical presentation of CMT may be unique or multiple, being the latter of the same or different histological type. The histopathological classification of tumors together with a brief description of their particular features is presented in this review. Although surgery is the best treatment for CMT, there are different adyuvant therapies that could improve the prognosis of the disease. The goal of the present work was to make an updated review of CMT, with special emphasis on its etiopathogy, treatment and new options resulting from the advances in molecular oncolo